Impact of obesity on clinical and angiographic characteristics in patients with ST-elevation myocardial infarction - Tharushika Promodini, Sinhasana Pattalegedara; Akilan, Saththiyanathan; Kalatsei, Liudmila (International Journal of Research in Medical Sciences, 2026)
Background: Obesity is a well-established cardiovascular risk factor and is strongly associated with metabolic dysregulation, systemic inflammation, and accelerated atherosclerosis. However, its influence on clinical presentation, laboratory parameters, and coronary angiographic characteristics in patients with ST-elevation myocardial infarction (STEMI) remains controversial. Methods: The study included 75 patients with STEMI who were admitted to the Grodno Regional Cardiological Center (Belarus) for treatment from July to October 2025. Patients were divided into two groups according to body mass index (BMI): group 1 (obese, BMI≥30 kg/m2; n=37) and group 2 (non-obese, BMI≤29.9 kg/m2; n=38). All patients underwent clinical, laboratory, and instrumental studies. Statistical analysis was performed using STATISTICA 12.0. Results: Obese patients had a significantly higher prevalence of diabetes mellitus compared with non-obese patients (35.13% versus 7.89%, p=0.04). They also demonstrated a distinct metabolic profile characterized by higher triglycerides (p=0.001) and lower HDL cholesterol concentrations (p=0.037). No significant differences were observed in cardiac biomarkers, or renal function parameters. Angiographically, involvement of the left anterior descending artery (p=0.025) and left circumflex artery (p=0.03) was more frequent in obese patients. The rate of percutaneous coronary intervention and the number of implanted stents were comparable between groups. Conclusions: Obesity in STEMI patients is associated with a higher burden of metabolic disturbances and more frequent multi-vessel coronary involvement, particularly affecting the left coronary system. These findings highlight the complex interaction between adiposity, metabolic dysregulation, and atherosclerotic severity in acute coronary syndromes.